Psychopathologic evidence in the Italian "Trap Music" population - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2022)
Background and aims: In the last decade, a musical strand has emerged in the Italian national scene that has international roots since the 1990s of the last century: "Trap Music" and younger generations are increasingly fascinated by this genre, for various reasons. The present research hypothesizes the existence of a link between the choice of preference of this musical genre and the psychopathological profile of those who choose their first preference, hypothesizing that such individuals have on average a higher level of dysfunctional traits typical of cluster B (borderline, narcissistic, histrionic and antisocial), according to the PICI model and compared to the population.  Materials and methods: Clinical interview, and administration of the battery of psychometric tests. The population sample was selected based on previous clinical contacts and voluntary participation through recruitment in major social networks (Facebook, Instagram, Twitter, TikTok), a total of 4,368 participants, divided into three age groups (18-25, 26-37, 38-46) and two groups (the first "clinical" and the second "control"). SPSS, Anova test (with Bonferroni). Results and discussion: On average, the users selected in the clinical group population sample presented 81% of cases with a psychopathological personality profile (PICI-2) with at least 5 dysfunctional traits afferent to cluster B (bipolar, borderline, histrionic, narcissistic, antisocial, and psychopathic) and at least 4 dysfunctional traits afferent to cluster C (paranoid, delusional, schizophrenic spectrum, dissociative), according to the PICI model, compared to 23.1% of the cases in the control group, which, however, shows traits more oriented toward neurotic tendencies (anxious, phobic-avoidant, obsessive, somatic). The investigation of dysfunctional sexual behaviors then showed, in the clinical group, the marked presence of the clinical condition of the users, with an average of 96.8% compared to 24% in the control group; in particular, the presence of a tendency toward pedophilic (under 13 years old) and pederastic (13-17 years old) paraphilia is noted for the average value between only the markings of the second and third clinical groups equal to 54.3% (with an overall phenomenon slightly more inclined toward the male group).  Conclusion: It is concluded, therefore, that the starting hypothesis can be confirmed, as the hypothesized link between the primary preference choice of "Trap Music" and the psychopathological profile afferent to the dysfunctional traits of Cluster B (borderline, narcissistic, histrionic, antisocial and psychopathic), according to the PICI model and compared with the control group (CG) population, which has significantly lower pathological values (57.9% - 72.8%) than the clinical group (CG), appears credible and non-random.